PHYSICAL DEVELOPMENT OF ARAK CITY APPLYING NATURAL INDICATORS. - Manijeh Ghahroudi TALI; Ali NAEIMI; Mahdieh ESFANDIARY (European Journal of Geography)
The purpose of this research is to evaluate the suitable areas for physical development of the Arak city in the future. Also, to found new physical index for developing of the city based on morphological features. For the objective, the spatial indicators of the analysis are climatology, topographic roughness coefficient, tectonic influenced factors, geomorphological landforms, land uses, runoff height and city relation with Mighan Desert which is located in the south of Arak City. TOPSIS and AHP models are majors Multi Criteria Evaluation models that have been used to prioritize the proposed areas. The results of the MCE analysis by AHP and TOPSIS indicated that the first priority for the physical development is an area in the east and northwest part of Arak City that was in parallel with Arak municipality plan for urban development. Sediment analysis of suitable areas represented that the area is located in flood bed which has unfavorable conditions for the establishment of utilities.